Effects of niacin on endurance performance in cyclists - Heath, E. M.; Wilcox, A. R.; Lickliter, K. L.; Kornatz, K. W. (Medicine & Science in Sports & Exercise, 1996)
Large doses of niacin, a B vitamin, reduces fat utilization during exercise. Studies of the effects of niacin on endurance performance have produced conflicting results, due, in part, tot he range of exercise intensities used in these studies. Therefore, the purpose of this study was to evaluate the effects of niacin on endurance performance at both moderate-and high-intensity exercise in the same subjects. Five highly-trained male endurance cyclists (height 181.8 +- 5.8cm; mass 75.5 +-7.2 kg; age 27.8 +- 3.6 yr: peak oxygen consumption (VO2 peak) 4.7 +- 0.33 L/min; body fat 10.2 +- 3.8%) participated in four time-to-exhaustion rides at approximately 68% and 86% of their VO2 peak. The work rates were equivalent for both trials at each of the two intensities. In a randomized, counterbalanced design, 1 g of niacin was ingested 1 h before one of the trials at each intensity. Time to exhaustion was significantly reduced in the niacin trials at 68% VO2 peak (101.6 +- 40.2 vs. 142.3 +- 51.0 min: p<.05), while there was no effect during the 86% VO2 peak trials (13.9 +- 6.5 vs. 20.3 +- 7.8 min, with and without niacin, respectively; p>.05). Niacin ingestion resulted in a significant reduction (p<.05) in pre- and post-serum FFA at both intensities except for post-serum FFA at 86% VO2 peak (p=.09). RER values were higher in the niacin trials at moderate intensity (.890 +- .038 vs. .918 +- .042), but were not significantly different (p=.078) and RER values were not significantly different (p>.05) at high intensity. As expected, the inhibition on FFA mobilization during the moderate intensity exercise caused a significant impairment in performance. However, at the higher intensity exercise, where fat utilization plays a lesser role, the inhibiting effects of niacin on FFA availability did not result in a statistically significant difference in performance times.